FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kaloko, Elsayrona Br; Deliana, Deliana (LPPM Universitas Bina Bangsa, 2025)
This study aims to determine the influence of auditor opinion, firm size and leverage on audit delay. The data used in this study is secondary data in the form of annual reports of mining companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sampling method uses purposive sampling, so that as many as 115 research data from 23 companies were obtained. The test was carried out using multiple linear regression analysis with the help of statistical package for the social sciences (SPSS) software version 25. Before conducting regression analysis, classical assumption testing is first carried out. The results of this study show that firm size and leverage have an effect on audit delay while auditor opinion has no effect on audit delay